In situ soft tissue regeneration using periosteal distraction: A preliminary study in the rat calvarial model - Osama Zakaria (Saudi Dental Journal, 2021)
Aim: In this study, we aimed to evaluate soft tissue generated by periosteal distraction. Background: Management of soft tissue defects represents a challenge in dentistry. Previous periosteal distraction studies documented partial fill of the distraction space with newly-generated bone and fibrous connective tissue. Material and methods: Titanium meshes were inserted in subperiosteal tunnels in the calvaria of 20 rats through coronal incision. The devices were immediately activated after insertion by elevation of one side at 1 mm/day for 3 days. Rats were then divided into two groups (n = 10). Animals were sacrificed after 2 weeks (Group 1) and after 4 weeks (Group 2). Distraction sites specimens were embedded in paraffin and analyzed histologically and histomorphometrically. Results: In both groups, new periosteum was regenerated and covered the original bone surface in the distraction site. Distraction spaces showed a predomination of hyper-vascularized connective tissue and little new bone formation near to the stable end of the device. The 4-week findings showed more organized collagen fibers with less vascularity compared to the 2-week findings. Conclusion: The periosteal distraction technique can effectively regenerate connective tissue. It may open a new modality in the guided tissue regeneration for soft tissue augmentation.